Design and test of a capacitance detection circuit based on a transimpedance amplifier*Project supported by the National Natural Science Foundation of China (No. 61127008) and the Subsidized Program of the National High Technology Research and Development Program of China (No. 2011AA040404). (July 2015) - Mu, Linfeng; Zhang, Wendong; He, Changde; Zhang, Rui; Song, Jinlong; Xue, Chenyang
Abstract This paper presents a transimpedance amplifier (TIA) capacitance detection circuit aimed at detecting micro-capacitance, which is caused by ultrasonic stimulation applied to the capacitive micro-machined ultrasonic transducer (CMUT). In the capacitance interface, a TIA is adopted to amplify the received signal with a center frequency of 400 kHz, and finally detect ultrasound pressure. The circuit has a strong anti-stray property and this paper also studies the calculation of compensation capacity in detail. To ensure high resolution, noise analysis is conducted. After optimization, the detected minimum ultrasound pressure is 2.1 Pa, which is two orders of magnitude higher than the former. The test results showed that the circuit was sensitive to changes in ultrasound pressure and the distance between the CMUT and stumbling block, which also successfully demonstrates the functionality of the developed TIA of the analog-front-end receiver.